ACROKERATOSIS VERUCIFORMIS OF HOPF CLINICALLY MIMICKING AS NECROLYTIC ACRAL ERYTHEMA - KAUR, SUKHPAL; GARG, MONIKA; SINGH, HARPAL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Acrokeratosis verruciformis is very rare genodermatosis that was originally described by Hopf in 1931. A 29-years-old male presented to skin outpatient department with brown-colored hyperkeratotic plaques on dorsum of both feet that clinically mimicked as necrolytic acral erythema in our case. Biopsy was taken from lesion that shows hyperkeratosis, acanthosis, and slight papillomatosis along with well-circumscribed elevation of epidermis resembling church spires. No dyskeratotic cells were seen.